Support Recovery from Noisy Measurement via Orthogonal Multi-Matching Pursuit. Issue 2 (24th May 2016) - Dan, Wei
Abstract: In this paper, a new stopping rule is proposed for orthogonal multi-matching pursuit (OMMP). We show that, for ℓ 2 bounded noise case, OMMP with the new stopping rule can recover the true support of any K -sparse signal x from noisy measurements y = Ф x + e in at most K iterations, provided that all the nonzero components of x and the elements of the matrix Ф satisfy certain requirements. The proposed method can improve the existing result. In particular, for the noiseless case, OMMP can exactly recover any K -sparse signal under the same RIP condition.